Prevalence of metabolic syndrome associated factors in the adult in UAE: effect of gender and age - Harfil, Sondos; AbuOdeh, Raed; Abdel-Rahman, Wael; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Jan Mohamed, Hamid Jan (Wiley, 2020)
Background: There’s a noticeable prevalence of metabolic syndrome (MetS) in the United Arab Emirates (UAE). Information is deficient on gender- and age-specific patterns and the prevalence of MetS along with the associated factors in the adult population. Objectives:: The aims of this study were to investigate the (1) gender-specific prevalence of MetS by its component and (2) the prevalence of MetS, and it’s component abnormalities by age group < 40 and > 40 years in UAE adults. Methods: A cross-sectional study was performed on 272 adults in Sharjah, UAE (Mean age, 34 ; 39.3% males, 60.7% females). Anthropometric measurements were collected (i.e. blood pressure, waist circumference, weight, and height). Fasting blood samples were analyzed to measure highdensity lipoprotein cholesterol(HDL), triglyceride (TG), fasting blood glucose, IL-6, hs-CRP and TNF- and insulin resistance (HOMA-IR). Results: 25% of the adults were diagnosed with Mets with higher prevalence in males (55.9%) compared to females (44.1%). 69.1.3% of the participants diagnosed with Mets were < 40 years, while they represent 17.2% of the participants in this study. Considering the Mets associated factors, blood pressure, waist circumference, HDL, TG, fasting blood glucose, hs-CRP and HOMA-IR were significantly higher in males (p < 0.001). Conclusions: Metabolic syndrome is predominant in the representative population in Sharjah, UAE, with visible gender and age pattern. The prevalence of Mets in the younger age group < 40 years is a critical factor that requires attention in order to prevent the progress of the cardiovascular diseases associated with Mets in the population.